Can obesity be prevented in the current obesogenic environment? - Swinburn, Boyd (Henry Stewart Talks, 2007)
Drivers of the obesity epidemic, Obesogenic environments, Lessons learned from other epidemics, Addressing "hosts", "vectors" and "environments", Whole-of-community intervention programs